(untitled) (Interdisciplinary Studies Journal, 2026)
This article analyze the memories of teachers who taught during the Covid-19 pandemic in Elementary School II, in the municipality of Itapetinga, state of Bahia. The main goal of the research is to understand the impact of social isolation on the work process of these teachers. The work is characterized as a research with an exploratory qualitative method, using historical-dialectical materialism as its approach, which allowed a critical investigation of the relationships between teaching work, historical context and socio-economic conditions during the pandemic. The rapid adaptation to technologies as the main resource for the teaching-learning process has triggered several challenges for teachers, such as rapid changes in routine, changes in teaching methodologies, increased workload and the accumulation of tiredness and stress, which in turn has given rise to or emphasized problems related to the mental and emotional health of this category. The results indicate that teaching work in this context was deeply affected by work overload, lack of institutional support, and the forced adaptation to remote teaching, which led many teachers to physical and mental illness, with effects that persist to this day.